República, tierra y comunidad de indios De las Cortes de Cádiz a Bolívar, Piura-Catacaos, siglo XIX 1 - Espinoza Claudio, Cesar (2008)
Landowners and small indigenous farmers were present in Piura’s society and economy in order to construct an agrarian system that allows this coastal region of the north of Peru to take place and start its development in the first decades of the 19th century. This essay tries to introduce us in the discussions of the progress in the productive border and the delivery of the public lands to the indigenous villages in a historical time of political crisis that goes from the Spanish Parliament of Cadiz to Simón Bolívar’s governmental work. To achieve this objective, we check the produced bibliography and systematize the information and file materials with the purpose of examining the particularities and the dynamics of an indigenous political culture that reasserts both life and history of the men of Catacaos village.